Health-resort complex development as a part of preventive medicine in the context of providing well-being - Nestorenko, Tetyana; Tokarenko, Olena; Nestorenko, Oleksandr (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The present paper analyses current state of health-resort industry in Ukraine. We define possibilities for its improvement according to the foreign experience. Subject of the paper consists in setting of organizational, economic, administrative mechanisms to ensure the functioning and development of health-resort complexes. In the paper special attention is paid to the functional structure of governing health-resort organizations, structure of a resort (spa) complex, and scheme of a consumer proceeding during the consumption of resort (spa) medical service while staying at Ukrainian health resort. Some significant aspects of international experience of organizing medical spa industry are observed. The research allows to formulate recommendations aimed to enhance further innovative development of health tourism as a ground for providing well-being of people
Keywords: uzdrowiska; spa; turystyka zdrowotna; balneoturystyka